IMPLEMENTASI BELAJAR MENGAJAR MATEMATIKA SEKOLAH DI IMMANUEL BONANG [THE IMPLEMENTATION OF SCHOOL MATHEMATICS TEACHING LEARNING IN IMMANUEL BONANG] - Oce Datu Appulembang; Kurnia Putri-Sepdikasari Dirgantoro; Jacob Stevy Seleky (Universitas Pelita Harapan, 2020)
Guidance and assistance in learning are necessary for every child, whether it is for the students who have attended school or not. Most of the parents who live in the Bonang area can not fulfill this activity. Parents who have not be able to accompany their children in learning after school are caused several factors, namely cognitive inability of parents, the busyness of parents in work, and the inability of parents economically to send their children to learning center, and some are even do not trust some learning center. Mathematics education students are prepared in the field of school mathematics teaching and learning expertise. For them, this activity is a valuable opportunity to gain teaching experience, as well as learning to implement the theories that have been learned, both in terms of pedagogy and mathematics. The purpose of this community is as a place to synchronize students’ need to implement their learning practices with the needs of schoolchildren around Bonang. The activity is in the form of assistance at one of the residents’ houses in Bonang. The benefits of this assistance activity are felt by all parties, schoolchildren as learning participants receive learning guidance in terms of cognitive and character, parents who are assisted and feel happy to see children's development in education, and the tutors can directly learn to implement knowledge and practice teaching.BAHASA INDONESIA ABSTRACT: Bimbingan dan pendampingan belajar diperlukan oleh setiap anak, baik yang bersekolah maupun yang tidak bersekolah. Kegiatan tersebut belum dapat dipenuhi oleh sebagian besar orang tua yang berdomisili di daerah Bonang. Orang tua yang belum dapat mendampingi anak-anaknya dalam belajar sepulang sekolah disebabkan oleh beberapa faktor yaitu ketidakmampuan orang tua secara kognitif, kesibukan orang tua dalam bekerja dan ketidakmampuan orang tua secara ekonomi untuk mengikutsertakan anaknya di dalam bimbingan belajar yang bersifat komersial, bahkan ada yang kurang percaya pada bimbingan belajar tertentu. Mahasiswa pendidikan matematika dipersiapkan pada bidang keahlian belajar mengajar matematika sekolah. Bagi mahasiswa, kegiatan tersebut merupakan kesempatan yang berharga untuk mendapatkan pengalaman mengajar, sekaligus belajar untuk mengimplementasikan teori yang sudah dipelajari, baik dari segi pedagogy maupun keilmuan matematika. Tujuan dari kegiatan ini adalah sebagai wadah untuk mensinkronisasikan kebutuhan mahasiswa untuk mengimplementasikan praktik pembelajaran mereka dengan kebutuhan anak sekolah di sekitar Bonang. Adapun kegiatan bimbingan belajar tersebut diselenggarakan di rumah salah satu warga di Bonang. Manfaat kegiatan bimbingan belajar ini dirasakan oleh semua pihak, anak-anak sekolah sebagai peserta belajar mendapatkan bimbingan belajar dari segi koginitif dan karakter, orangtua yang terbantukan dan merasa bahagia melihat perkembangan anak dalam pendidikan dan mahasiswa pendidikan matematika yang menjadi tutor dapat secara langsung belajar mengimplementasikan ilmu dan praktek mengajarnya.